Grammar of the shot - Bowen, Christopher J.; Thompson, Roy. (2013)
"Tell effective visual stories by utilizing the "grammar of film and video with this elegant, modular reference. See what you absolutely need to know to put together your own film or video, shot by shot. Whether you're just learning how to frame a shot or simply looking for a refresher, Grammar of the Shot gives you a toolkit to help you build a successful visual story that flows smoothly. Understand the basic building blocks essential for successful shot lighting, screen direction, 3D elements, camera movement, and many general practices that make for richer, multi-layered visuals. Expand your visual vocabulary and help jumpstart your career in film and video. Get ample examples and further instruction on the new companion website.Designed as an easy-to-use reference, Grammar of the Shot presents each topic succinctly with clear photographs and diagrams illustrating the key concepts. Simple and easy to use, Grammar of the Shot is a staple of any filmmaker's library"--
Keywords: Cinematography -- Handbooks, manuals, etc; Composition (Photography) -- Handbooks, manuals, etc; PERFORMING ARTS / Film & Video / General